A novel process of the isolation of nitrifying bacteria and their development in two different natural lab-scale packed-bed bioreactors for trichloroethylene bioremediation. (1st July 2019) - Berrelleza-Valdez, Fernando; Parades-Aguilar, Jonathan; Peña-Limón, Carlos E.; Certucha-Barragán, María Teresa; Gámez-Meza, Nohemí; Serrano-Palacios, Denisse; Medina-Juárez, Luis Angel; Calderón, Kadiya
Abstract: Trichloroethylene (TCE) is a carcinogenic compound that is commonly present in groundwater and has been detected in drinking water sources for Mexican towns in the Mexico-US border area. Nitrifying bacteria, such as Nitrosomonas europaea, have been shown to be capable of degrading halogenated compounds, including TCE, but it is difficult to obtain high cell concentrations of these bacteria. The aim of the present study was to generate biomass of a nitrifying bacterial consortium from the sludge of an urban wastewater treatment plant (WWTP) and evaluate its capacity to biodegrade TCE in two different natural lab-scaled packed bed bioreactors. The consortium was isolated by a novel method using a continuous stirred-tank bioreactor inoculated with activated sludge from the Domos WWTP located in Cd. Obregón, Sonora, Mexico. The bioreactor was fed with specific media to cultivate ammonia-oxidizing bacteria at a dilution rate near the maximum specific growth rate reported for Nitrosomonas europaea . Optical density and suspended solids measurements were performed to determine the culture biomass production, and the presence of inorganic nitrogen species was determined by spectrophotometry. The presence of nitrifying ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) was confirmed by PCR amplification, and biofilm formation was observed by scanning electron microscopy. Batch-scale experiments confirmed the biodegradative activity of the isolated consortium, which was subsequently fixed in an inorganic carrier as zeolite and a synthetic carrier such as polyurethane to both be used as lab-scale packed-bed bioreactors, with up to 58.63% and 62.7% of TCE biodegradation achieved, respectively, demonstrating a possible alternative for TCE bioremediation in environmental and engineering systems. Graphical abstract: Image 1 Highlights: The isolation of nitrifying bacteria was achieved by a CSTB. The presence of ammonia-oxidizing and nitrite-oxidizing bacteria was detected. The bacteria isolated showed TCE biodegradative capacity in batch. Two different natural packed-bed bioreactors were fixed with the isolated bacteria. The bacteria isolated showed higher TCE degradation capacity in both bioreactors.